The relationship between CM and CO chondrites: Insights from combined analyses of titanium, chromium, and oxygen isotopes in CM, CO, and ungrouped chondrites. (15th May 2021) - Torrano, Zachary A.; Schrader, Devin L.; Davidson, Jemma; Greenwood, Richard C.; Dunlap, Daniel R.; Wadhwa, Meenakshi
Abstract: A close relationship between CM and CO chondrites has been suggested by previous petrologic and isotopic studies, leading to the suggestion that they may originate from similar precursor materials or even a common parent body. In this study, we evaluate the genetic relationship between CM and CO chondrites using Ti, Cr, and O isotopes. We first provide additional constraints on the ranges of ε 50 Ti and ε 54 Cr values of bulk CM and CO chondrites by reporting the isotopic compositions of CM2 chondrites Murchison, Murray, and Aguas Zarcas and the CO3.8 chondrite Isna. We then report the ε 50 Ti and ε 54 Cr values for several ungrouped and anomalous carbonaceous chondrites that have been previously reported to exhibit similarities to the CM and/or CO chondrite groups, including Elephant Moraine (EET) 83226, EET 83355, Grosvenor Mountains (GRO) 95566, MacAlpine Hills (MAC) 87300, MAC 87301, MAC 88107, and Northwest Africa (NWA) 5958, and the O-isotope compositions of a subset of these samples. We additionally report the Ti, Cr, and O isotopic compositions of additional ungrouped chondrites LaPaz Ice Field (LAP) 04757, LAP 04773, Lewis Cliff (LEW) 85332, and Coolidge to assess their potential relationships with known carbonaceous and ordinary chondrite groups. LAP 04757 and LAP 04773 exhibit isotopic compositions indicating they are low-FeO ordinary chondrites. The isotopic compositions of Murchison, Murray, Aguas Zarcas, and Isna extend the compositional ranges defined by the CM and CO chondrites in ε 50 Ti versus ε 54 Cr space. The majority of the ungrouped carbonaceous chondrites with documented similarities to the CM and/or CO chondrites plot outside the CM and CO group fields in plots of ε 50 Ti versus ε 54 Cr, Δ 17 O versus ε 50 Ti, and Δ 17 O versus ε 54 Cr. Therefore, based on differences in their Ti, Cr, and O isotopic compositions, we conclude that the CM, CO, and ungrouped carbonaceous chondrites likely represent samples of multiple distinct parent bodies. We also infer that these parent bodies formed from precursor materials that shared similar isotopic compositions, which may indicate formation in regions of the protoplanetary disk that were in close proximity to each other.